Back-action supercurrent rectifiers - Daniel Margineda; Alessandro Crippa; Elia Strambini; Laura Borgongino; Alessandro Paghi; Giorgio de Simoni; Lucia Sorba; Yuri Fukaya; Maria Teresa Mercaldo; Carmine Ortix; Mario Cuoco; Francesco Giazotto (Communications Physics)
Abstract Back-action refers to a response that retro-acts on a system to tailor its properties with respect to an external stimulus. This effect is at the heart of many electronic devices such as amplifiers, oscillators, and sensors. Here, we demonstrate that back-action can be exploited to achieve non-reciprocal transport in superconducting circuits. In our devices, dissipationless current flows in one direction whereas dissipative transport occurs in the opposite direction. Supercurrent diodes presented so far rely on magnetic elements or vortices to mediate charge transport or external magnetic fields to break time-reversal symmetry. Back-action solely turns a conventional reciprocal superconducting weak link with no asymmetry between the current bias directions into a rectifier, where the critical current amplitude depends on the bias sign. The self-interaction of the supercurrent stems from the gate tunability of the critical current in metallic and semiconducting systems, which promotes nearly ideal magnetic field-free rectification with selectable polarity.